2023
DOI: 10.1039/d2nr05930d
|View full text |Cite
|
Sign up to set email alerts
|

Synergistically boosting the anchoring effect and catalytic activity of MXenes as bifunctional electrocatalysts for sodium–sulfur batteries by single-atom catalyst engineering

Abstract: MXenes based sulfur hosts have attracted enormous attention in room temperature sodium-sulfur (RT Na-S) batteries due to their strong affinity towards soluble sodium polysulfides (NaPSs). However, their electrocatalytic performance needs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…However, Na 2 Se 8 exhibits a larger adsorption energies than Na 2 S 8 . Among the SACs studied in this work, Fe@rg-C 3 N 4 presents the strongest interaction for both Na-pSs and Na-pSes, with adsorptions energies surpassing numerous previously reported 2D sulfur hosts like graphene, 64 MXenes, 65 VS 2 , 66 and As 2 S 3 . 67 Additionally, we have also computed the adsorption energy for Na 2 X 3 species on pristine, reduced g-C 3 N 4 , and Fe SAC as shown in Fig.…”
Section: Adsorption Of Xmentioning
confidence: 43%
See 1 more Smart Citation
“…However, Na 2 Se 8 exhibits a larger adsorption energies than Na 2 S 8 . Among the SACs studied in this work, Fe@rg-C 3 N 4 presents the strongest interaction for both Na-pSs and Na-pSes, with adsorptions energies surpassing numerous previously reported 2D sulfur hosts like graphene, 64 MXenes, 65 VS 2 , 66 and As 2 S 3 . 67 Additionally, we have also computed the adsorption energy for Na 2 X 3 species on pristine, reduced g-C 3 N 4 , and Fe SAC as shown in Fig.…”
Section: Adsorption Of Xmentioning
confidence: 43%
“…S11 †. The interaction energies (0.58–0.81 eV) 65 between Na–pXs and DOL/DME are significantly lower than the adsorption energies (1.65–3.83 eV) of Na–pXs on SACs, suggesting that these SACs can effectively preclude Na–pXs shuttling in Na–S and Na–Se batteries.…”
Section: Resultsmentioning
confidence: 99%
“…The results are consistent with the previous research, which indicated that the interaction between sulfur-containing species and the anchoring materials could be dramatically enhanced by introducing TMs. 61,62 In summary, the improved interaction of non-polar (001) surfaces was attributed to lithiophilic and sulfiphilic characteristics of TMCs (i.e. the co-formation of S-TM and Li-C interaction).…”
Section: The Adsorption Of S 8 and Lipss On The Tmc (001) Surfacementioning
confidence: 96%
“…28 Interestingly, the discovery of graphene spurred considerable interest in the usage of two-dimensional (2D) materials with unique structures and excellent remarkable properties as AMs for metal-sulfur batteries. [29][30][31][32] In this context, functionalized graphene, 33 C 2 N, 34 MXenes, [35][36][37] single-atom catalysts supported by 2D nanomaterials, [38][39][40] vanadium disulfide monolayers, 21 and doped borophosphene 22 have been proposed as sulfur hosts for Na-S batteries.…”
Section: Introductionmentioning
confidence: 99%